Peningkatan Kesadaran Lingkungan Masyarakat Melalui Program Edukasi Melalui Media Ecobin: Studi Kasus Di Kelurahan Padang Jati - Pradhana, Bhagawanta Atyuta; Epriantravolta Saragih; Wahyu Putra; Hafidza Zia (CV. ITTC INDONESIA, 2025)
The waste problem is a crucial issue that is increasing along with population growth, which also causes an increase in waste volume and the need for waste disposal. If not managed properly, waste can cause various negative impacts such as the spread of disease, unpleasant odors, and decreased environmental aesthetics. For this reason, Bengkulu University KKN students period 105 Group 56 held an outreach activity for the Padang Jati Village community with the aim of providing education about wise waste management. This activity involved lectures, discussions, and waste sorting demonstrations. As a result, the community began to understand how to sort waste properly, realized the negative impacts of unmanaged waste, and learned the benefits of waste processing, which ultimately raised awareness of the importance of maintaining environmental cleanliness starting from themselves and the surrounding environment.